A team approach to anterior lumbar spine surgery in the military. (August 2014) - Dua, Anahita; Fox, Jennifer; Patel, Bhavin; Martin, Eric; Rosner, Michael; Fox, Charles J
We report a five year military experience with anterior retroperitoneal spine exposure combining vascular and neurosurgical spine teams. From August 2005 through April 2010 (56 months), hospital records from a single institution were retrospectively reviewed. Complications, estimated blood loss, transfusions, operative time and length of stay were documented. Eighty-four patients with lumbar spondylosis underwent primary (63, 75%) or secondary exposure (21, 25%) of a single- (66, 79%) or multilevel disc space (18, 21%). Median operative time and estimated blood loss were 127 minutes (range, 30–331 minutes) and 350 mL (range, 0–2940 mL). The overall complication rate was 23.8%. Postoperative complications included six blood transfusions (7%), three patients with retrograde ejaculation (3.57%) or surgical site infection; two with a prolonged ileus (2.38%) or ventral hernia and one each with a bowel obstruction (1, 1.19%), deep venous thrombosis or lymphocele. All-cause mortality was 1%. In conclusion, a team approach can minimize complications while offering the technical benefits and durability of an anterior approach to the lumbar spine.